SOSIALISASI PENGOLAHAN KOTORAN TERNAK SAPI MENJADI BIOGAS DI DESA RANJOK KABUPATEN LOMBOK BARAT - Ronia, Ronia; Sahbudin, Muhammad; Kuswari, Zeta; Pacitra, Silda; Febriana, Dina; Kurniawati, Kurniawati; Anggriani, Nining; Fernanda, Muhammad; Apriandi, Doni; Samad, Abdul; Nurnaningsih, Ratna; Muanah, Muanah; Ihromi, Syirril (Jurnal Agro Dedikasi Masyarakat (JADM), 2021)
Cow dung is one of the wastes that can disturb the environment. The volume that continues to increase without handling can cause disease, especially during the rainy season. So seeing these conditions, socialization was carried out to increase the knowledge and skills of the community in processing cow dung waste into biogas. The method or activity steps are the preparation, socialization, and evaluation stages. The results of the activity showed that the socialization activity with the theme of utilizing cow manure into biogas received a good response from all circles of society, especially members who were members of the human-informed cattle group and from the village of Ranjok itself. The socialization activity was attended by 23 people who enthusiastically participated in the activity until the end. The results of the evaluation by conducting interviews that the community is ready to be involved in biogas production training activities by applying biodigester technology. In addition, with the knowledge and skills that the community has independently, they can process cattle waste into biogas so that the volume of waste can be reduced and biogas can be utilized.